Mini review of spatially fractionated radiation therapy for cancer management - Shrikant B. Mali (Oral Oncology Reports)
Spatially fractionated radiation therapy (SFRT) is a non-uniform dose distribution technique that has shown high rates of clinical response with minimal toxicities in large-volume primary or metastatic malignancies. However, prospective multi-institutional clinical trials in SFRT are lacking, and SFRT techniques and dose parameters remain variable. A consensus on dose prescription, technical administration, and clinical and translational design parameters for SFRT trials is essential to enable broad participation and successful accrual to rigorously test the SFRT approach. The field of radiotherapy aims to develop techniques that allow for greater tumor control and better sparing of critical organs. Investigations into the complexity of tumor radiobiology have confirmed the high heterogeneity of tumors as responsible for poor treatment outcomes. Hypoxic subvolumes, a subpopulation of cancer stem cells, and inherent or acquired radioresistance define tumour aggressiveness and metastatic potential, which remain a therapeutic challenge. Non-conventional irradiation techniques, such as SFRT, have been developed to tackle some of these challenges and offer a high therapeutic index when treating radioresistant tumors. Preclinical findings showed that the high-single-dose irradiation of hypoxic tumor cells generates a stronger bystander effect (BE) and AE than the normoxic cells, suggesting their higher “immunogenic potential.'' This led to the development of a novel Stereotactic Body RadioTherapy (SBRT)-based PArtial Tumor irradiation targeting HYpoxic segment (SBRT-PATHY) for induction of the immune-mediated BE and AE. Encouraging SBRT-PATHY-clinical outcomes, along with immunohistochemical and gene-expression analyses of surgically removed abscopal-tumor sites, suggested that delivery of the high-dose radiation to the partial tumor volume, with optimal timing based on the homeostatic fluctuation of the immune response and sparing the peritumoral immune-environment, would significantly enhance the immune-mediated anti-tumor effects.